Selection of an Appropriate Particulate Matter (PM) Separation Device for a Proposed Waste Incineration Plant - Yakah, Noah; Kwarteng, Augustine Akuoko; Addy, Cyrus; Yirenkyi, Michael; Aklie, Jonas (European Journal of Technology, 2024)
Purpose: Waste incineration facilities are the most widely used Waste to Energy (WtE) technology employed in developed economies in the disposal and management of Municipal Solid Waste (MSW). A major drawback of waste incineration facilities is the enormous volume of toxic emissions emitted from these facilities. Particulate Matter (PM) is a complex combination of either solid or liquid particulates produced from the combustion of MSW that are suspended in the air. These particles which are carcinogenic are therefore required to be separated from the emissions from the waste incineration plants prior to its emission into the atmosphere. Materials and Methods: The cyclone, fabric filter, and Electrostatic Precipitators are typical PM separation devices that are employed in conventional coal-fired power generation plants. The adoption of these devices in waste incineration plants therefore require studies to select an appropriate one for use. In this study various models of the waste incineration plants were simulated using the Aspen Plus software aim at selecting an appropriate PM separation device for use in a proposed waste incineration plant in Ghana. Findings: The study concluded that the fabric filter and the ESP are the optimum PM separation devices, achieving an overall separation efficiency of 99.54% and 99.45 % respectively for all particle sizes. The fabric filter was therefore, adopted for use in the proposed waste incineration plant. Implications to Theory, Practice and Policy: It is recommended, however, that a techno-economic analysis is performed on the use of the fabric filter and ESP in the proposed waste incineration facility.